THE EFFECT OF EGG FEEDING ON SERUM THIAMINE LEVELS IN CHILDREN WITH STUNTING USING THE ENZYME-LABELLED PROTEIN LIGAND ASSAY (ELPLA) METHOD - Andi Alelda Rara Fatimah; Dwirini Retno Gunarti (RADJA PUBLIKA, 2026)
Stunting is a chronic nutritional problem that remains a public health challenge in Indonesia and is associated with impaired linear growth, metabolic changes, and micronutrient deficiencies, including thiamine (vitamin B1). As an essential cofactor in energy metabolism, thiamine deficiency has the potential to exacerbate growth impairments in stunted children. This study aimed to assess thiamine levels using plasma samples from stunted children aged 24–59 months who had received a 30-day egg intervention and to compare them with healthy children. Thiamine levels were measured using the Enzyme-Labeled Protein Ligand Assay (ELPLA), an alternative method that is simpler and more economical than instrumental methods such as HPLC and fluorometry. The results showed that the mean thiamine levels increased from 1.06 ± 1.95 µg/mL to 3.76 ± 1.51 µg/mL after the intervention (p<0.001). Thiamine levels in stunted children before the intervention were lower than those in normal children (6.33 ± 0.57 µg/mL; p < 0.001) and remained lower after the intervention (p < 0.001). Thus, one month of egg consumption was associated with an increase in serum thiamine levels in stunted children, but it was not yet sufficient to restore levels to those of normal children.